Managing risks in business travel - Pajula, Emmi (My University, 2018)
Companies are utilizing business travel in their operations. At the same time, the risk levels of travel are increasing, which exposes business travelers to a variety of serious risks. Therefore, this thesis seeks to understand, how companies can manage the health and security risks their employees face on their business trips. To provide a framework for the study, the theory chapter of this thesis discusses business travel related health and security risks, travel management and risk management. The empirical research of this thesis is an exploratory case study that seeks to understand the management process by investigating it from different perspectives. The data is collected using semi-structured interviews and analysis of travel and risk documents. This data is then analyzed and discussed comparing it to the previous literature. The findings suggest that the process of managing travel related health and security risks requires versatile cooperation with several stakeholders. Careful planning, considering several risks and taking different management measures is also needed. In addition, the research showed the importance of the traveler in this process. Their education and involvement to the process is essential to make it possible for the management process to work in practice.
Keywords: Business travel; Travel management; Risk management; fi=Johtaminen ja organisaatiot|en=Management and Organization|